Exploring the perceived factors that affect self-medication among nursing students: a qualitative study - Ali Soroush; Alireza Abdi; Bahare Andayeshgar; Afsoon Vahdat; Alireza Khatony (BMC, 2018)
Abstract Background Self-medication is the use of one or more medications without physician's diagnosis, opinion, or prescription and supervision, which includes the use of herbal or chemical drugs. Todays, self-medication is one of the biggest socio-health and economic problems among nursing students of various societies, including Iran, and because this issue can affected by contextual factors, this study aimed to explore the perceived factors that affect self-medication among nursing students. Methods In this qualitative study, a semi-structured interview was conducted with 11 nursing students. The transcript of each interview was reviewed several times and classified into main categories and sub-categories by content analysis. To evaluate this study, Guba and Lincoln's four criteria, including credibility, transferability, dependability, and confirmability were considered for trustworthiness. Results After analyzing the qualitative content of the interviews, four main categories, including educational backgrounds, nature of the disease, access to the media, and beliefs and personal experiences, and ten subcategories, including contact with clinical environment, relative knowledge about medications, simplicity of the disease, recurrence of the disease, influence of the media, use of the internet, believing in own knowledge, positive experiences of traditional medicine, and using own and others' experiences, were extracted. Conclusions It seems that, having a relative awareness about various diseases and medications, which is sometimes associated with taking a few educational courses with an internship, creates a false confidence in student for self-medication and prescribing drugs to others. It would be beneficial if the education system and associated tutors could inform the students about the possible consequences of this issue. By knowing the internal and subjective factors that influence the self-medication, this arbitrary practice can be largely prevented.